Bacterial Community Associated with Healthy and Diseased Pacific White Shrimp (Litopenaeus vannamei) Larvae and Rearing Water across Different Growth Stages - Zheng, Yanfen; Yu, Min; Liu, Jiwen; Qiao, Yanlu; Wang, Long; Li, Zhitao; Zhang, Xiao-Hua; Yu, Mingchao (Frontiers in Microbiology, 2017)
Bacterial communities are called another “organ” for aquatic animals and their important influence on the health of host has drawn increasing attention. Thus, it is important to study the relationships between aquatic animals and bacterial communities. Here, bacterial communities associated with Litopenaeus vannamei larvae at different healthy statuses (diseased and healthy) and growth stages (i.e. zoea, mysis and early postlarvae periods) were examined using 454-pyrosequencing of the 16S rRNA gene. Bacterial communities with significant difference were observed between healthy and diseased rearing water, and several bacterial groups, such as genera Nautella and Kordiimonas could also distinguish healthy and diseased shrimp. Rhodobacteraceae was widely distributed in rearing water at all growth stages but there were several stage-specific groups, indicating that bacterial members in rearing water assembled into distinct communities throughout the larval development. However, Gammaproteobacteria, mainly family Enterobacteriaceae, was the most abundant group (accounting for more than 85%) in shrimp larvae at all growth stages. This study compared bacterial communities associated with healthy and diseased L. vannamei larvae and rearing water, and identified several health- and growth stage-specific bacterial groups, which might be provided as indicators for monitoring the healthy status of shrimp larvae in hatchery.